Urban Growth Shadows in Mainland China - Yin, Shuaibo. (Tufts University. Tisch Library., 2024)
Thesis (M.S.)--Tufts University, 2024.; Submitted to the Dept. of Economics.; Advisor: Yannis Ioannides.; Committee: Yannis Ioannides, and Adam Storeygard.; Keywords: Economics, Geography, and Transportation.